Kesulitan Siswa SMP dalam Menyelesaikan Soal Literasi Membaca Berorientasi HOTS pada Mata Pelajaran IPS - Iwin Listiana Kusmaryanti; Yumi Hartati (Varied Knowledge Journal, 2026)
This study aims to identify the factors causing student’s difficulties in solving HOTS oriented reading literacy questions based on question characteristic, literacy skill, and teacher’s learning strategies. Furthermore, this study analyzes test items to determine the cognitive berorientasi and the type of question stimulus considered most difficult by students.The research method used is quantitative with descriptive statistical analysis. The research sample includes eighth grade students at SMP Negeri 1, 2, and 3 Gemolong, Sragen Regency. The research instruments consist of HOTS oriented reading literacy questions for social studies, questionnaires, and school documents, which have been validated using the SPSS application and expert validation. The results indicate that the student’s highest difficulty berorientasis are at the evaluating (C5) and creating (C6) berorientasis. Overall, the question difficulty berorientasi and student’s reading literacy skills are I the moderate category. Internal factors, which serve as the main causes of student’s difficulties, include the inability to analyze, limited vocabulary, and difficulty finding implicit information. Meanwhile, external factors include the learning environment and teacher’s learning strategies. Based on these results, social studies learning should improve student’s reading through analytical, evaluative, and creative reasoning, as well as establishing continuous reading literacy habits